Effects of subtotal pancreatectomy and long‐term glucose and lipid overload on insulin secretion and glucose homeostasis in minipigs - Rébecca Goutchtat; Audrey Quenon; Manon Clarisse; Nathalie Delalleau; Anaïs Coddeville; Mathilde Gobert; Valéry Gmyr; Julie Kerr‐Conte; François Pattou; Thomas Hubert (Endocrinology, Diabetes & Metabolism, 2023)
Abstract Introduction Nowadays, there are no strong diabetic pig models, yet they are required for various types of diabetes research. Using cutting‐edge techniques, we attempted to develop a type 2 diabetic minipig model in this study by combining a partial pancreatectomy (Px) with an energetic overload administered either orally or parenterally. Methods Different groups of minipigs, including Göttingen‐like (GL, n = 17) and Ossabaw (O, n = 4), were developed. Prior to and following each intervention, metabolic assessments were conducted. First, the metabolic responses of the Göttingen‐like (n = 3) and Ossabaw (n = 4) strains to a 2‐month High‐Fat, High‐Sucrose diet (HFHSD) were compared. Then, other groups of GL minipigs were established: with a single Px (n = 10), a Px combined with a 2‐month HFHSD (n = 6), and long‐term intraportal glucose and lipid infusions that were either preceded by a Px (n = 4) or not (n = 4). Results After the 2‐month HFHSD, there was no discernible change between the GL and O minipigs. The pancreatectomized group in GL minipigs showed a significantly lower Acute Insulin Response (AIR) (18.3 ± 10.0 IU/mL after Px vs. 34.9 ± 13.7 IU/mL before, p < .0005). In both long‐term intraportal infusion groups, an increase in the Insulinogenic (IGI) and Hepatic Insulin Resistance Indexes (HIRI) was found with a decrease in the AIR, especially in the pancreatectomized group (IGI: 4.2 ± 1.9 after vs. 1.5 ± 0.8 before, p < .05; HIRI (×10−5): 12.6 ± 7.9 after vs. 3.8 ± 4.3 before, p < .05; AIR: 24.4 ± 13.7 µIU/mL after vs. 43.9 ± 14.5 µIU/mL before, p < .005). Regardless of the group, there was no fasting hyperglycemia. Conclusions In this study, we used pancreatectomy followed by long‐term intraportal glucose and lipid infusions to develop an original minipig model with metabolic syndrome and early signs of glucose intolerance. We reaffirm the pig's usefulness as a preclinical model for the metabolic syndrome but without the fasting hyperglycemia that characterizes diabetes mellitus.